A Decade of Porous Silicon as Nano‐Explosive Material. Issue 3 (7th November 2013) - Plessis, Monuko du
Abstract: It is a decade since the accidental discovery of the room temperature explosive properties of porous silicon, impregnated with a solid state oxidizer, was communicated in 2002 [1]. A significant amount of research and development have followed this announcement, leading to an innovative explosive technology that may be on the verge of being applied in a number of applications. It is thus now an opportune time to reflect on the progress of this new technology over the last decade. Just in the last two years, there has been a significant increase in the number of research papers reporting on new developments and exciting new applications. In this paper the technological development of porous silicon explosive devices is reviewed, a decade of technological research and development documented, and the current state of the technology evaluated. The most important aspects of the technology are presented, device performance characteristics are investigated and different applications are considered. Typical device design and manufacturing techniques are highlighted that actually resulted in reliable explosive behavior. The information in this paper should serve as a source of reference not only for researchers already active in this field, but also to new researchers starting or contemplating to exploit this technology. Abstract :